Transcript Complexity and New Insights of Restorer Line in CMS-D8 Cotton Through Full-Length Transcriptomic Analysis - Feng, Juanjuan; Li, Yongqi; Zhang, Jinfa; Zhang, Meng; Zhang, Xuexian; Shahzad, Kashif; Guo, Liping; Qi, Tingxiang; Tang, Huini; Wang, Hailin; Qiao, Xiuqin; Lin, Zhongxu; et al. (Frontiers in Plant Science, 2022)
Hybrid utilization has proficiently increased crop production worldwide. The cytoplasmic male sterility (CMS) system has emerged as an efficient tool for commercial hybrid cotton seed production. The restorer line with dominant Rf2 gene can restore the fertility of the CMS-D8 sterile line. However, the molecular mechanism of fertility restoration remains unclear in CMS-D8 cotton that limits wider utilization of three-line hybrid breeding. In our study, the Pacific Biosciences (PacBio) Iso-Seq technology was applied to understand fertility restoration mechanism of CMS-D8 cotton. In total, 228,106 full-length non-chimeric transcriptome sequences were obtained from anthers of developing flowering buds. The analysis results identified 3,174 novel isoforms, 2,597 novel gene loci, 652 long non-coding RNAs predicted from novel isoforms, 7,234 alternative splicing events, 114 fusion transcripts, and 1667 genes with alternative polyadenylation. Specially, two novel genes associated with restoration function, Ghir_D05.742.1 and m64033_190821_201011/21103726/ccs were identified and showed significant higher levels of expression in restorer line than sterile and maintainer lines. Our comparative full length transcriptome analysis provides new insights into the molecular function of Rf2 fertility restorer gene. The results of this study oﬀers a platform for fertility restoration candidate gene discovery in CMS-D8 cotton.